Pelaksanaan Hukum Waris Islam pada Masyarakat di Desa Wonosalam Kabupaten Jombang - Nasrullah, Syahri Bangkit (Universitas Sebelas Maret, 2023)
This study describes and examines the implementation of inheritance distribution in the Islamic community in Wonosalam Village and the influence of Islamic boarding schools on the distribution of inheritance in Islamic communities in Wonosalam Village. This research is a descriptive socio-legal research law. Types of data include primary and secondary data with data collection techniques used are observation and interviews, then analyzed by descriptive method. The results showed that the distribution of inheritance in the Islamic community in Wonosalam Village there were two inheritance laws used, namely Islamic inheritance law and customary inheritance law which were carried out by deliberation. The existence of a boarding school that has been established since 1974 has influenced the Islamic community in Wonosalam Village in the distribution of inheritance. Although the distribution of inheritance to the Islamic community in Wonosalam Village is carried out according to custom, based on tasaluh this is allowed, with the aim of not causing conflict between families.